(untitled) (Applied Biological Research, 2023)
Gloriosa superba L., an important medicinal plant, is included in the list of endangered plants so needs a special attention for its conservation through micropropagation. An efficient in vitro regeneration protocol was established using tubers as explants. Briefly, surface sterilized explants were cultured on MS medium containing different concentrations and combinations of 6-benzylaminopurine (BAP), kinetin and 1-naphthal eneacetic acid. Highest shoot regeneration frequency (88%) was recorded in MS medium containing 2.0 mg L-1 BAP. Half strength MS media supplemented with indole-3-acetic and indole-3-butyric acid (IBA), either alone or in combination, were used for rooting. Highest root regeneration (71%) was recordein 2.0 mg L-1IBA. Genetic fidelity of in vitro-raised plants was evaluated using RAPD and ISSR molecular markers, as there is always a danger of somaclonal variations in tissue culture technology. Out of the 17 (10 random amplified polymorphic DNA (RAPD) and 7 inter simple sequence repeats (ISSR) primers screened, 2 RAPD and 2 ISSR primers produceclear, distinct and reproducible amplicons. The results revealed genetic homogeneity and true-to-type nature of in vitro raised plants using RAPD and ISSR analysis. The developed protocol may prove helpful in regenerating valuable resource material for easy growth.